2015
DOI: 10.1111/are.12841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the formulated diet MySpat for feeding hatchery-reared spat of the green-lipped mussel,Perna canaliculus(Gmelin, 1791)

Abstract: As with most bivalves, a high cost component of hatchery and nursery culture of the green‐lipped mussel (Perna canaliculus) is the raising of live micro‐algae feeds. To remedy this, artificial feeds have been developed, however, these have had mixed success for this species. In this experiment, we tested the formulated diet MySpat (sourced from INVE Aquaculture) on P. canaliculus spat of approximately 1 mm in size. Performance measures under study were mussel spat growth and survivorship after 21 days feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 14 publications
0
42
2
Order By: Relevance
“…Juvenile oysters in hatcheries today are fed on microalgal diets, a system which brings many challenges. First, growing live microalgae in hatcheries accounts for 50% of production costs at US$220 per kg biomass in 2016 (Gui et al, 2016b; Knauer and Southgate, 1999). Second, the microalgae produced are of highly variable and often poor nutritional quality for the oysters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juvenile oysters in hatcheries today are fed on microalgal diets, a system which brings many challenges. First, growing live microalgae in hatcheries accounts for 50% of production costs at US$220 per kg biomass in 2016 (Gui et al, 2016b; Knauer and Southgate, 1999). Second, the microalgae produced are of highly variable and often poor nutritional quality for the oysters.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the microalgae produced are of highly variable and often poor nutritional quality for the oysters. Third, algal cultures are susceptible to frequent contamination by bacteria which can result in sudden and dramatic population crashes (Gui et al, 2016b; Luzardo-Alvarez et al, 2010). Fourth, feeds can be a major vector of disease, and complete batches of oysters are often lost, sometimes leading to hatchery closure (Prado et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies recognised lipids to be the main energy stores for bivalves up to 6 months post-settlement [25, 26]; Since then, evaluating the lipid composition of diets and juveniles gained a central importance on bivalve nutrition studies with examples available for clams [2733], scallops [3436], oysters [3742] and mussels [19, 4346]. Other than protein and carbohydrate composition, the nutritional properties of shellfish diets strongly depend on the essential PUFA (arachidonic acid – 20:4n-6, AA; eicosapentaenoic acid – 20:5n-3, EPA; docosahexaenoic acid – 22:6n-3, DHA) content [47].…”
Section: Introductionmentioning
confidence: 99%
“…Researches on the nutritional requirements and artificial feed of bivalve molluscs are relatively more laggard than those on other aquatic animals (fish, shrimp and crab) . A few studies have reported the development of artificial diets in several bivalve species, such as microalgal concentrates (Brown & Robert, 2002), spray-dried microalgae (Arney, Liu, Forster, Mckinley & Pearce, 2015), single-cell detritus production from seaweeds (Tanyaros & Chuseingjaw, 2016), yeasts (Nell, Diemar & Heasman, 1996), microcapsules of varying types (Chu, Webb, Hepworth & Casey, 1987;Knauer & Southgate, 1997;Numaguchi, 2002;Numaguchi & Nell, 1991), bacterial proteins (Philippe & Christopher, 1994) and formulated diets (Gui, Kaspar, Zamora, Dunphy & Jeffs, 2016b;Gui, Zamora, Dunphy & Jeffs, 2016a;Mamat & Alfaro, 2014;Nevejan, Davis, Little & Kiliona, 2007;Nevejan, Pronker & Peene, 2008;Wang et al, 2016;Yang, Luo, Wang, Deng & Du, 2015a;Yang et al, 2015b). However, no artificial feed has been commercially and biologically reliable to substitute for live microalgal feed for pearl oyster.…”
mentioning
confidence: 99%